Post-disaster reconstruction in Medellin informal settlements and the associated resilience dimensions of place-remaking - Benjumea, Diana (2020)
In urban planning research, studies that investigate the process of reconstruction after natural disasters in Latin American countries, and the set of resilience coping strategies organically developed by residents of these areas, are very limited. In Colombia, for instance, the lack of understanding on how these communities have reshaped the built environment through grassroots actions has amplified the gaps between the historical development of urban slums and the principles for the latest top-down participatory urban developmental strategies. In response, this thesis aims to reveal the process of development of an informal settlement, Villatina located at the Comuna 8 in Medellin Colombia that has followed a long process of reconstruction after a major landslide in 1987. The main resilience community aspects created during the reconstruction are unveiled and discussed against the backdrop of the outbreak of civil war in the 1990s, which significantly affected the informal settlements of Medellin.